2021
DOI: 10.1007/s00253-021-11250-w
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of SARS-CoV-2 genome using different nanopore chemistries

Abstract: Nanopore sequencing has emerged as a rapid and cost-efficient tool for diagnostic and epidemiological surveillance of SARS-CoV-2 during the COVID-19 pandemic. This study compared the results from sequencing the SARS-CoV-2 genome using R9 vs R10 flow cells and a Rapid Barcoding Kit (RBK) vs a Ligation Sequencing Kit (LSK). The R9 chemistry provided a lower error rate (3.5%) than R10 chemistry (7%). The SARS-CoV-2 genome includes few homopolymeric regions. Longest homopolymers were composed of 7 (TTTTTTT) and 6 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Using the improved ARCTIC protocol ( 21 ), we were able to obtain high accuracy genomes from most of the samples. Various recent studies similarly reported the successful use of nanopore platforms to obtain SARS-CoV-2 whole-genome sequences ( 10 , 37 , 38 ), and thousands of SARS-CoV-2 genomes submitted to GISAID were derived solely from nanopore sequencing. This demonstrates that the nanopore platform is able to generate adequately accurate SARS-CoV-2 sequence data for real-time downstream analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Using the improved ARCTIC protocol ( 21 ), we were able to obtain high accuracy genomes from most of the samples. Various recent studies similarly reported the successful use of nanopore platforms to obtain SARS-CoV-2 whole-genome sequences ( 10 , 37 , 38 ), and thousands of SARS-CoV-2 genomes submitted to GISAID were derived solely from nanopore sequencing. This demonstrates that the nanopore platform is able to generate adequately accurate SARS-CoV-2 sequence data for real-time downstream analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sequencing platform has received a major improvement in accuracy with the new R10.3 flowcell in pair with new basecalling tool (Bonito) 21 . The accuracy has been validated in several studies showing improvements in both consensus 22 and sequencing accuracy 23 , including sequencing accuracy for the homopolymer region 22 , 24 . With the improved accuracy, index sequences can be shortened to minimize dimer formation, which should improve PCR efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In January 2020, the original protocol was promptly adjusted for rapid sequence determination of SARS-CoV-2 RNA prepared directly from clinical samples such as nasopharyngeal or oropharyngeal swabs. Additional studies described its modifications including alternative primer schemes and different amplicon sizes or different sequencing chemistries (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Its further improvements resulted in simplification of the sequencing library preparation, shortened hands-on time, and increased sample multiplexing (up to 96) that decreased the reagent costs to about £10 per sample, making this approach affordable for epidemiologic surveillance of the pandemics (36).…”
Section: Introductionmentioning
confidence: 99%
“…schemes(27), custom synthesized by Microsynth). The same cycling program was used for all amplicon types (i.e.,30 sec initial denaturation at 98 o C, followed by 25 to 35 cycles of 15 sec at 98 o C (denaturation) and 5 min at 65 o C (combined annealing and polymerization), and cooling to 4 o C). The amplifications were performed in two separate reactions and the…”
mentioning
confidence: 99%